Three-dimensional brain-like microenvironments facilitate the direct reprogramming of fibroblasts into therapeutic neurons. (July 2018) - Jin, Yoonhee; Lee, Jung; Kim, Jin; Min, Sungjin; Wi, Soohyun; Yu, Ji; Chang, Gyeong-Eon; Cho, Ann-Na; Choi, Yeeun; Ahn, Da-Hee; Cho, Sung-Rae; Cheong, Eunji; et al.
Abstract Biophysical cues can improve the direct reprogramming of fibroblasts into neurons that can be used for therapeutic purposes. However, the effects of a three-dimensional (3D) environment on direct neuronal reprogramming remain unexplored. Here, we show that brain extracellular matrix (BEM) decellularized from human brain tissue facilitates the plasmid-transfection-based direct conversion of primary mouse embryonic fibroblasts into induced neuronal (iN) cells. We first show that two-dimensional (2D) surfaces modified with BEM significantly increase the generation efficiency of iN cells and enhance neuronal transdifferentiation and maturation. Moreover, in an animal model of ischaemic stroke, iN cells generated on the BEM substrates and transplanted into the brain led to significant improvements in locomotive behaviours. We also show that compared with the 2D BEM substrates, 3D BEM hydrogels recapitulating brain-like microenvironments further promote neuronal conversion and potentiate the functional recovery of the animals. Our findings suggest that 3D microenvironments can boost nonviral direct reprogramming for the generation of therapeutic neuronal cells. Hydrogels made from decellularized human brain tissue facilitate the direct conversion of primary mouse embryonic fibroblasts into induced neuronal cells that lead to therapeutic outcomes after transplantation in an animal model of ischaemic stroke.